Pengaruh Beban Kerja terhadap Produktivitas Kerja Karyawan Pada PT. Bank BTPN Syariah Cabang Bangkinang - Zaman, Deffian; Putri Agusdina (Bedelau: Journal of Education and Learning, 2021)
Bank Tabungan Pensiunan Nasional Syariah is a financial institution that is specifically focused on serving the poor or underprivileged people. The problem in this research is that the realization of the performance of PT. Bank BTPN Syariah Bangkinang Branch in 2015-2019 is still below the target that has been compiled in the company's Annual Budget Work Plan (RKAT). In 2015 the target was only achieved 75% of the business plan set by the company, then in 2016 the realization was achieved 66.67%, in 2017 there was a very good performance synergy, this can be seen from the realization of the achievement of performance reaching 100.41% of the target. determined by the company, in 2018 the realization of the achievement decreased to 83.33%, The purpose of this study was to determine the workload on the work productivity of employees at PT. Bank BTPN Syariah Bangkinang Branch. This research was conducted using quantitative descriptive research methods. Data were obtained through direct interviews and questionnaires to respondents, and then the data were analyzed and processed using quantitative descriptive methods. Based on the results of data analysis from observation and distribution of questionnaires to respondents, the authors conclude that the value of tcount (2.351)> t table (2.008), then H0 is rejected, H1 is accepted. It can be concluded that there is a positive and significant influence between workload programs on employee work productivity at PT. Bank BTPN Syariah, Bangkinang Branch. Based on testing the coefficient of determination. R of 0.400 means that the influence of workload variables on employee work productivity variables is 40.0%. This means that the relationship is close. Keywords: Workload, Work Productivity